1986
DOI: 10.1093/infdis/153.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomally Mediated Resistance in Neisseria gonorrhoeae in the United States: Results of Surveillance and Reporting, 1983-1984

Abstract: Between January 1983 and October 1984, 446 cases of infection due to chromosomally mediated resistance in Neisseria gonorrhoeae (CMRNG) were reported in 23 states. Eighty percent were detected as primary penicillin or ampicillin treatment failures. Gonococcal isolates were submitted from 175 (40%) for confirmation of resistance, susceptibility testing, gonococcal strain typing using monoclonal antibodies specific for outer membrane Protein I, and auxotyping. All were typed as Protein I serogroup IB (WII/WIII),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Decreased susceptibility to the expanded-spectrum cephalosporins such as cefoxitin and cefuroxime has also developed (12,18). In the present study, chromosomally mediated resistance to penicillin G and tetracycline and decreased susceptibility to cefoxitin were highly correlated with increased MICs of ceftriaxone.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Decreased susceptibility to the expanded-spectrum cephalosporins such as cefoxitin and cefuroxime has also developed (12,18). In the present study, chromosomally mediated resistance to penicillin G and tetracycline and decreased susceptibility to cefoxitin were highly correlated with increased MICs of ceftriaxone.…”
Section: Discussionsupporting
confidence: 56%
“…Previous work by others has suggested an association between protein I serovar and chromosomally mediated resistance to antibiotics (18,24). The pattern of serovar-auxotypes found in a community is not stable from year to year (17,21), and clonal outbreaks of particular strains may occur (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the men, 91 strains were cultured from the urethra, 5 from the urethra and pharynx, 1 from the pharynx, and 3 from the rectum. Among the women, 11 strains were cultured from the cervix alone, 12 from the cervix and the rectum, 4 from the rectum alone, and 2 from the cervix and pharynx. When multiple sites were infected or colonized in the same patient, the MICs for all the strains were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Gonococcal strains that are resistant to penicillin, tetracycline, and the cephalosporins have been isolated (20,25). A strain belonging to the A/S class Pro/IB-1 and resistant to penicillin, tetracycline, erythromycin, and cefoxitin was isolated during an epidemic of gonorrhea in North Carolina in 1984 (20 ever, showed that strains belonging to several A/S classes exhibited chromosomal resistance to antimicrobial agents (25,48).…”
Section: Gonococcal Strain Populations In Communitiesmentioning
confidence: 99%